Arquegenealogia bajubeira: uma análise de práticas de poder e resistência - (:unkn) unknown (Universidade Federal de Goiás, 2020)
Submerged within the Discourse Analysis (AD) of French line, this dissertation, whose research uses qualitative and theoretical-descriptive-analytical methodology, deals with the understanding of bajubá as resistance to the heterocisnormative device from the works of Michel Foucault. Based on the questioning of the philosopher “who are we today?”, In The subject and the power (1995), this study concerns the contemporary subject, more precisely the bajubeiro subject. Considering Foucault's commitment to attesting that the exercise of power is not dissociated from the practices of resistance, this work aims to demonstrate this functioning from the counter-conduct of some Education professionals. It is also a question of certifying this same functioning through escape practices, seeking to understand how the subjects are subjectified in order to perform paradigmatic identities and how the bajubeiro subject, considered abject within this system, resists through the bajubá. Therefore, this production analyzes the power games referring to the expressions and roles of sex / gender in the current Brazilian society, having as a corpus a great discursive event, the proof of the ENEM 2018, in which a question about the bajubá discursive object emerges, enabling the establishment of an associated field, functioning as a possibility condition so that this question could appear in the exam. For that, in an archegenealogical and cartographic endeavor, a theoretical-methodological instrument of Discourse Analysis is used to think about the processes of subjectification related to sexuality issues as a result of a socio-historical discursive construction. The results obtained point out that resistance to heterocysnormativity occurs through permanent confrontations, and not through the search for absolute freedom, since, in Foucault's perspective, this is not possible to accomplish. As the bajubá is a powerful technique of subjectivation, this confrontation takes place by combating essentialist gender thinking and heterocysnormativity, either through counter-conducts or through a “self-care” technique; that is, the bajubeiro subject performs subversive identities, experimenting with other modes of conduct, in a work of himself on himself, in a process of fighting against subjectivities developed from the conception that physiological factors determine sexuality in all its dimensions.
Bajubeira archegenealogy: an analysis of power and resistance practices
Keywords: Análise do discurso foucaultiana; Relações de poder; Processo de subjetivação; Bajubá; Sujeito bajubeiro; Foucault's Discourse analysisd; Power relations; Subjectivation process; Subject bajubeiro; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA